Future projections of seasonal temperature and precipitation for India - Salunke, Popat; Keshri, Narayan Prasad; Mishra, Saroj Kanta; Dash, S. K. (Frontiers in Climate, 2023)
Ninety climate models, from four consortiums — CMIP5, CMIP6, NEX-GDDP, and CORDEX — are evaluated for the simulation of seasonal temperature and precipitation over India, and subsequently, using the best ones, their future projections are made for the country. NEX-GDDP is found to be the best performer for the simulation of surface air temperature for all the four seasons. For the simulation of precipitation, CMIP6 performs the best in DJF and MAM seasons, whilst NEX-GDDP is the best in JJAS and ON seasons. The selected models suggest that temperature will increase over the entire Indian landmass, relatively more over the northwestern part of the country. Further, the rate of warming will be more in winter than in summer. The models also suggest that precipitation will increase, over central eastern and north eastern India in the monsoon season, and over peninsular India during post monsoon months.